Regulating the Topologies and Photoresponsive Properties of Lanthanum‐Organic Frameworks - Ren, Xin‐Ye; Chen, Fan‐Yao; Zhang, Chun‐Hua; Liang, Zhen‐Gang; Yu, Xiao‐Yue; Han, Song‐De; Wang, Guo‐Ming (Chemistry : a European journal, 2024)
Metal‐organic frameworks (MOFs) show potential application in many domains, in which photochromic MOFs (PMOFs) have received enormous attention. Researchers mainly utilize photoactive ligands to build PMOFs. Recently, the mixed electron donating and accepting ligands strategies have also been used to construct PMOFs driven by the electron transfer between nonphotochromic moieties. However, the potential interligand competition inhibits the formation of PMOFs. Therefore, the exploration of single‐ligand‐guided assembly is conductive for building PMOFs. Considering the existing electron accepting and donating role of pyridyl and carboxyl, the pyridinecarboxyate derived from the fusion of pyridyl and carboxyl units may serve as single ligand to yield PMOFs (Figure 1d). In this work, the coordination assembly of bipyridinedicarboxylate (2,2′‐bipyridine‐4,4′‐dicarboxylic acid, H2bpdc; 1,10‐phenanthroline‐2,9‐dicarboxylic acid, H2pda) and LaCl3 generate two PMOFs, [La(bpdc)(H2O)Cl] (1) and [La(pda)(H2O)2Cl]⋅2H2O (2). Both complexes feature dinuclear lanthanum as building blocks with differences in the connecting number of likers, in which 1 has (4,8)‐connected topology and 2 exhibits sql topology. Their structural differences result in the diversities of photoresponsive functionalities. Compared with reported PMOFs built from photoactive ligands and mixed ligands, this study provides new available categories of single ligand for generating PMOFs and tuning the structure and photoresponsive properties via ligand substitution and external photostimulus. Two lanthanum‐organic frameworks with dinuclear lanthanum as building blocks and distinct bipyridinedicarboxylate as likers are prepared. Their structural differences result in the diversities of photoresponsive functionalities in terms of photochromism, photomodulated fluorescence and proton conductivity.